A systematic review and meta-analysis of patient education in preventing and reducing the incidence or recurrence of adult diabetes foot ulcers (DFU) - Adiewere, P.; Gillis, Richard B.; Imran Jiwani, S.; Meal, Andrew; Shaw, Ian; Adams, Gary G. (Elsevier, 2018)
Background